An essay on blindness: mental health in primary care and disputes in the face of the pandemic of covid-19 - Mattos, Mússio Pirajá; Pereira, Beatriz Medrado; Gomes, Daiene Rosa (Saúde e Sociedade, 2022)
Primary health care (PHC) is an important resource for facing issues associated with psychological distress. Thus, this essay aims to discuss mental health (MH) in PHC in the face of the covid-19 pandemic. Besides bringing to light old problems related to the assistentialist and medicalized logic of the MH care, the pandemic upholds practices that underutilize and disregard PHC potentialities as a care provider in a political-economic scenario of power struggle, which encourages the privatization of public services. Such power play influences care provision, especially in chaotic scenarios of injustices and inequalities – fertile ground for covid-19 spread. This context evinces the need for taking a closer look at the effects of MH on PHC, since managers, professionals, and users can be plunged into the so-called “white blindness”. Thus, recognizing the legitimacy of knowledge, values, and desires that move different types of workers and users is crucial; that is, understanding MH as a relational field in constant movement. Likewise, bringing a glimmer of hope by promoting reflections that turn on the lights so that this care approaches integral care is also important.